Enhancing Moral Development in Early Childhood: Evidence from Effective Learning Practices - Jagneet Kaur; Elizabeth Ifeoma Anierobi; Gorica Popovska Nalevska; Mohammed Xolile Ntshangase; Tomas Shivolo; Doris Chasokela; Erepamowei Diri; Muhammad Abdul Latif; Kudakwashe Manokore (Nak-Kanak: Journal of Child Research, 2026)
Background of the study: Moral values encompass teachings about good and bad behavior, attitudes, duties, ethics, and manners that shape a child's future role in society. Early Childhood Education (ECE) occurs during the golden age, a critical period when children are highly receptive to learning and habit formation. Through repeated exposure to good behavior, children can be shaped into individuals of noble character. Therefore, teachers play a key role in guiding learners to internalize strong moral values, which contribute not only to their moral integrity but also to their intellectual development. Aims and scope of paper: This study explores how moral and religious values are instilled in children through Islamic-based early childhood education at RA Al-Amien. It focuses on the learning strategies employed by educators, the integration of Islamic teachings into the curriculum, and observable behavioral outcomes in children that reflect moral development. Methods: This qualitative study utilized passive participant observation, semi-structured interviews, and document analysis. Informants included the principal, teachers, and students at RA Al-Amien. Data were analyzed following the Miles and Huberman model, involving data reduction, data display, and conclusion drawing. Results: RA Al-Amien consistently integrates Islamic teachings across six domains of child development. Children are guided to memorize prayers and Hadiths, demonstrate respectful behavior toward adults, and show kindness to peers. This structured moral training supports the development of akhlaqul karimah (noble character). Contribution: Islamic-based early childhood education at RA Al-Amien effectively promotes moral and religious development. Through daily practice and teacher guidance, children show measurable progress in internalizing moral development, reinforcing the value of moral education in early formative years.